Push-Out Bond Strength of Quartz Fiber Posts Luted with Self-Adhesive and Conventional Resin Cements - Cardoso, Luiz; Araújo DDS, MSD, PhD, Élito; Narciso Baratieri DDS,MSD, PhD, Luiz; Ramírez DDS, MSD, PhD, Juan (Odovtos - International Journal of Dental Sciences, 2016)
The aim of this study was to evaluate the influence of the resin cement on push-out bond strength of quartz fiber posts to intraradicular dentin. Fifty-six single-rooted human teeth were selected. After removing the crown, roots were endodontically treated and the dowel spaces were prepared with # 2 post drills of DT Ligth® SL Post System (VDW®). The specimens were randomly divided into four groups (n = 14). Group 1: RelyX™ Unicem (3M ESPE), Group 2: Clearfil ™ SA Cement (Kuraray), Group 3: Bifix SE (Voco), and G4 RelyX™ ARC (3M ESPE). After 24 h, 12 specimens of each group were sectioned in 6 slices with 1 mm of thickness, two of each radicular third. The push-out test was conducted in an Instron machine at 0.5 mm/min. Data were submitted to ANOVA and Bonferroni test. Fractured specimens were observed at 25X to evaluate the types of failures. Two specimens of each group were processed for SEM evaluation. The Mean values (MPa) for groups 1, 2, 3 and 4 were respectively: 11.06, 8.85, 8.37 and 13.36. All experimental groups showed higher values of resistance in the cervical third, while the lowest were in the apical third. Adhesive failures between cement and dentin (46.87 %) prevailed, followed by mixed failures (45.15 %). SEM photomicrographs illustrating the interface formed between the self-adhesive resin cements and dentin showed an interface without the formation of a hybrid layer. G4 showed the formation of a thick and homogeneous hybrid layer with resin tags. The conventional resin cement associated with a three-step adhesive system displayed the higher bond strength to intraradicular dentin, when compared to the different self-adhesive resin cements.